Lioness : Golda Meir and the nation of Israel - Klagsbrun, Francine (Schocken Books, 2017)
"The definitive biography of Golda Meir: the iron-willed leader, chain-smoking political operative, and tea-and-cake-serving grandmother who became the fourth prime minister of Israel and one of the most notable women of our time"--